A Lettered Utopia: Printed Alphabets and the Material Republic of Letters. (2020) - Fuchs, Barbara; Palmer, Philip S.
Abstract : Several early editions of Thomas More's "Utopia, " first published in 1516, include the Utopian alphabet, as well as a quatrain of poetry in Utopian and its Latin transliteration. This essay traces the material conditions for the Utopian alphabet, exploring the intellectual contexts and epistemological questions that underlie its presence in these early editions and its absence in others. Reproduced by four early modern European printers via woodcut, metal type, or engraved plate, the alphabet in its materiality becomes a key component of "Utopia, " underscoring the intersection between print technology and an expansive humanism extending to ever wider intellectual and geographic horizons.